Fatty acid utilisation and metabolism in caecal enterocytes of rainbow trout (Oncorhynchus mykiss) fed dietary fish or copepod oil - Oxley, Anthony; Tocher, Douglas R; Torstensen, Bente E; Olsen, Rolf E (Biochimica et Biophysica Acta (BBA) - Molecular and Cell Biology of Lipids, 2005)
A combined fatty acid metabolism assay was employed to determine fatty acid uptake and relative utilisation in enterocytes isolated from the pyloric caeca of rainbow trout. In addition, the effect of a diet high in long-chain monoenoic fatty alcohols present as wax esters in oil derived from Calanus finmarchicus, compared to a standard fish oil diet, on caecal enterocyte fatty acid metabolism was investigated. The diets were fed for 8 weeks before caecal enterocytes from each dietary group were isolated and incubated with [1-14C]fatty acids: 16:0, 18:1n-9, 18:2n-6, 18:3n-3, 20:1n-9, 20:4n-6, 20:5n-3, and 22:6n-3. Uptake was measured over 2 h with relative utilisation of different [1-14C]fatty acids calculated as a percentage of uptake. Differences in uptake were observed, with 18:1n-9 and 18:2n-6 showing the highest rates. Esterification into cellular lipids was highest with 16:0 and C18 fatty acids, accounting for over one-third of total uptake, through predominant incorporation in triacylglycerol (TAG). The overall utilisation of fatty acids in phospholipid synthesis was low, but highest with 16:0, the most prevalent fatty acid recovered in intracellular phosphatidylcholine (PC) and phosphatidylinositol (PI), although exported PC exhibited higher proportions of C20/C22 polyunsaturated fatty acids (PUFA). Other than 16:0, incorporation into PC and PI was highest with C20/C22 PUFA and 20:4n-6 respectively. Recovery of labelled 18:1n-9 in exported TAG was 3-fold greater than any other fatty acid which could be due to multiple esterification on the glycerol ‘backbone’ and/or increased export. Approximately 20-40% of fatty acids taken up were β-oxidised, and was highest with 20:4n-6. Oxidation of 20:5n-3 and 22:6n-3 was also surprisingly high, although 22:6n-3 oxidation was mainly attributed to retroconversion to 20:5n-3. Metabolic modification of fatty acids by elongation-desaturation was generally low at